2007
DOI: 10.4049/jimmunol.178.3.1457
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Virus Infection Causes Global Respiratory Tract B Cell Response Modulation via Innate Immune Signals

Abstract: Induction of primary B cell responses requires the presence of Ag and costimulatory signals by T cells. Innate signals further enhance B cell activation. The precise nature and kinetics of such innate immune signals and their functional effects are unknown. This study demonstrates that influenza virus-induced type I IFN is the main innate stimulus affecting local B cells within 48 h of infection. It alters the transcriptional profile of B cells and selectively traps them in the regional lymph nodes, presumably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 49 publications
6
71
0
Order By: Relevance
“…Previous reports demonstrated that type I IFN mediates activation of LN-resident B cells in response to influenza or West Nile virus infection (48)(49)(50)(51). In the context of West Nile virus infection, the authors excluded macrophages as type I IFN-producing cells, but the actual cellular source was not identified for either infection model.…”
Section: Discussionmentioning
confidence: 89%
“…Previous reports demonstrated that type I IFN mediates activation of LN-resident B cells in response to influenza or West Nile virus infection (48)(49)(50)(51). In the context of West Nile virus infection, the authors excluded macrophages as type I IFN-producing cells, but the actual cellular source was not identified for either infection model.…”
Section: Discussionmentioning
confidence: 89%
“…At this time, we cannot exclude other mechanisms that may also contribute to the enhanced Ab response in G9KO mice. For instance Gal-9 deficiency may limit other mechanisms of suppression (25), resulting in increased levels of factors that act directly on B cells to promote their activation (26).…”
Section: Discussionmentioning
confidence: 99%
“…Rotavirus infection promoted substantial T-cell-independent B-cell activation by day 3 in the mesenteric lymph nodes (LN) in wild-type mice (6,7). Polyclonal B-cell activation and virus-specific antibody responses against influenza virus were dependent on type I interferon (IFN) signaling (11,13). In contrast, B-cell activation of mediastinal LN after murine gammaherpesvirus 68 infection was delayed until day 10 and required T-cell help (52).…”
mentioning
confidence: 99%